The role of motivation in the employee’s job performance A field study on insurance companies in Lattakia Governorate)) - محمد زينب; حنان تركمان; لمى إسبر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to study the role of motivation among employees of insurance companies in Lattakia Governorate in their performance, studying the level of motivation among employees and the level of performance they enjoy in these companies. The researcher relied on the analytical approach as a general method for the approach, as it relied on the comprehensive inventory method in distributing the research questionnaire, (156) questionnaires were distributed, of which (154) were valid for statistical analysis. Then, the researcher used the 26Spss statistical analysis program as a tool for analyzing the available data, conducting statistical descriptions, and testing research hypotheses. The results showed that the employees in the insurance companies in Lattakia governorate enjoy a high level of motivation and performance, and the researcher concluded that there is a positive significant effect of the level of motivation among members of the research community on their performance.